Using root water uptake estimated by a hydrological model to evaluate the least limiting water range - Gubiani,Paulo Ivonir (2020)
ABSTRACT The least limiting water range (LLWR) has been extensively determined, but evaluating if LLWR can indeed indicate soil physical stress on plant growth is still a controversial issue. In this study, we used the Hydrus-1D hydrological model to simulate root water uptake (RWU) to analyze if RWU and LLWR are correlated under stress conditions. The LLWR was determined in a sandy-loam Ultisol and a clayey Oxisol. In both soils, RWU extracted by plants (leaf area index set as 3) from a rooted layer of 0.4 m was simulated over 20 days under a potential evapotranspiration rate of 6 mm day-1. For each soil, RWU was simulated over the same range of soil compaction in which LLWR was determined. The cumulative RWU over the 20 days varied between 23 to 58 mm in the Ultisol and 20 to 48 mm in the Oxisol, indicating that plants were able to take up only a small part of the cumulative potential transpiration (93 mm) and experienced severe water stress in some soil conditions. However, RWU under water stress was poorly correlated with both bulk density and LLWR. The correlation between RWU and LLWR was 0.5 (p<0.01) for the Ultisol and 0.22 (p<0.19) for the Oxisol, suggesting that LLRW has little (for Ultisol) or almost no (for Oxisol) ability to indicate soil quality related to plant water availability. Our simulations suggest that RWU in the water availability range (between field capacity and wilting point) may be little affected or even improved by light soil compaction. Studies to elucidate this phenomenon would contribute to the understanding of the compaction effect on RWU and the weak correlation between RWU and LLWR.